Flora composition of wastewater receiving wetlands - Ten, Dennis Choon Yung (Universiti Malaysia Sarawak, (UNIMAS), 2001)
(_Wetlands are the Il1{)st productive ecosystem on earth. For generations, it plays an important role by perfonning certain functions. One of the functions of wetlands is act as a wastewater treatment facility with the present of plants. The survey conducted has shown that there are significant water quality changes as the wastewater flow through the wetland and there is five dominance plants species (Ipomea aquatica. Leersia hendra, &leria sumatrensis, Mikania micrantha and Commelina nudijlora) in UNIMAS cleared Peatswamp Forest. Out of these five dominance plant species, statistic indicated four of them are correlated higher with water quality parameters.) Those four plants are Ipomea aquatica, Leersia hendra, &leria sumatrensis and Mikani6 micrantha. &leria sumatrensis correlated highly with pH (r -0.681), ammonia-nitrogen (r '= 0529), nitrate (r '= -0.415) and chemical oxygen demand (r 0.621). Ipomea aquatica is correlated with pH (r = 0.414) and ammonia-nitrogen (r -0.417). While the Leersia hendra and Mikania micrantha are only correlated with biochemical oxygen demand and dissolved oxygen respectively. However, only Ipomea aquatica, &leria sematrensis and Leersia hendra are recommended plants in consl.lucted wetlands based on the high index from correlation analysis with water quality.